Subthalamic Deep Brain Stimulation With a New Device in Parkinson's Disease: An Open‐Label Trial. Issue 3 (28th March 2013) - Liu, Huan‐guang; Ma, Yu; Zhang, Kai; Ge, Ming; Meng, Fan‐gang; Feng, Tao; Wan, Xin‐hua; Guo, Yi; Wang, Ren‐zhi; Yang, An‐chao; Hu, Wen‐han; Guo, Jin‐zu; et al.
<x xml:space="preserve">Abstract</x> Objective We aimed to evaluate the safety and efficacy of subthalamic nucleus deep brain stimulation (STN‐DBS) with a new stimulator (Beijing PINS Medical Co., Ltd, PNS 1101) in Parkinson's disease (PD). Materials and Methods Forty patients received a PINS device implantation in the subthalamic nucleus. The effects of stimulation on motor score, activities of daily living, good‐quality on‐time, and the levodopa‐equivalent dose were analyzed for all 40 patients with PD treated with bilateral or unilateral STN‐DBS. The scores were collected at baseline in two conditions (on/off medication) and at 3, 6, 9, 12, and 24 months of follow‐up with stimulation in the absence or presence of medication. The patients were followed up for two years. Results At 3, 6, 9, 12, and 24 months of follow‐up, our results showed a significant increase from baseline in both activities of daily living and motor scores (p < 0.001) and good‐quality on‐time (p < 0.001); the daily levodopa‐equivalent dose decreased compared with baseline (p < 0.01). No patient died during the study, and none of the adverse effects were classified as severe. All of the adverse events were resolved or improved by the end of the study. Conclusions STN‐DBS with the PINS device significantly improved the symptoms of PD when compared with baseline in this trial. This new device may be recommended for the treatment of patients with advanced PD; however, a randomized, double‐blinding trial will be required.